Synthesis of Oil Palm Fronds Charcoal as Adsorbent to Reduce Levels of Fe (III) in Peat Water - Rahmat Zikri; Evelin Natasyah; Muhdarina Muhdarina (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The high content of carbon compounds in palm fronds (OPF) makes them potentially useful as an adsorbent. The carbonization method was used for the adsorbent synthesis process. This process began with collecting palm frond waste and then drying and sifting the adsorbent particle. This process resulted in the escape particles with a size of 80 mesh and suspended particles with 120 mesh. Then this process continued by carbonizing the palm fronds with temperature variations starting from (400, 500, and 600°C) for 60 minutes to obtain Charcoal Oil Palm Fronts (COPF). The obtained COPF was determined for moisture and ash content and characterized using FTIR, XRD, and SEM to determine the surface, functional groups, degree of amorphism, crystallinity, and surface morphology. The adsorption efficiency of COPF was applied to the adsorption of Fe (III) in peat water under varying contact time, adsorbent mass, and peat water volume conditions. The water and ash content of COPF qualify the technical quality requirements for activated charcoal according to SNI 06-3730-1995. FTIR analysis detected the presence of vibrations of the C-O, O-H, C=O, C-C, and C-H functional groups on the COPF surface. The XRD pattern showed the existence of a semi-crystalline (002) and (100) plane structure, which is shown at scattering angles of 2θ = 22o and 42o. The surface morphology of COPF showed that as the carbonization temperature increased, the number of pores formed increased, and the pore size decreased. The best adsorption test results were obtained with a contact time of 30 minutes, an adsorbent mass of 1.00 g, and a peat water volume of 100 mL. The highest Fe adsorption efficiency was achieved by COPF 500, where the adsorbed mass was 0.054 mg. Increasing the carbonization temperature causes the water content to decrease and the ash content to increase. High water content and ash content cause a decrease in adsorption efficiency because they can cover the pores of the adsorbent.